The Use of Critical Care Services After Orthopedic Surgery at a High-Volume Orthopedic Medical Center: A Retrospective Study. Issue 3 (August 2022) - Zhong, Haoyan; Garvin, Sean; Poeran, Jashvant; Liu, Jiabin; Kirksey, Meghan; Wilson, Lauren A.; DeMeo, Danya; Yang, Elaine; Hong, Genewoo; Jules-Elysee, Kethy M.; Nejim, Jemiel; Memtsoudis, Stavros G.
Background: With an aging population, orthopedics has become one of the largest and fastest growing surgical fields. However, data on the use of critical care services (CCS) in patients undergoing orthopedic procedures remain sparse. Purpose: We sought to elucidate the prevalence and characteristics of patients requiring CCS and intermediate levels of care after orthopedic surgeries at a high-volume orthopedic medical center. Methods: We retrospectively reviewed inpatient electronic medical record data (2016–2020) at a high-volume orthopedic hospital. Patients who required CCS and intermediate levels of care, including step-down unit (SDU) and telemetry services, were identified. We described characteristics related to patients, procedures, and outcomes, including type of advanced services required and surgery type. Results: Of the 50, 387 patients who underwent orthopedic inpatient surgery, 1.6% required CCS and 21.6% were admitted to an SDU. Additionally, 482 (1.0%) patients required postoperative mechanical ventilation and 3602 (7.1%) patients required continuous positive airway pressure therapy. Spine surgery patients were the most likely to require any form of advanced care (45.7%). Conclusions: This retrospective review found that approximately one-fourth of orthopedic surgery patients were admitted to units that provided critical and intermediate levels of care. These results may prove useful to hospitals in estimating needs and allocating resources for advanced and critical care services after orthopedic surgery.